Momentum Surat Al Lail dalam Perspektif Filsafat Bisnis - Muslimin (Dinar : Jurnal Prodi Ekonomi Syariah, 2022)
Al-Lail verses and letters are important in the ranks of business verses through this verse which are able to provide new arguments in the economic scene. Al-Qur'an and Hadith are two Muslim guidelines that are interconnected with each other. The current situation and the future situation are also full of science and technology needed by mankind. So that the Qur'an and Hadith are often referred to as the source of all knowledge, including business and muamalat issues. Some of the knowledge contained in the Qur'an is easy to understand, while others require further thought and development and reflection to be understood. One's understanding of the Qur'an depends on one's intelligence, so the same verse may give different interpretations. In this journal we discuss the relationship of Surat al-Lail on economics with its philosophy. The momentum of Surah Al-Lail is a Makiyyah letter that was revealed to the Prophet shalallahu 'alaihi wasallam before moving to the city of Medina, and the subject of this letter is related to people who donate and people who are stingy. As well as motivation for business movements with various theories and practices. Keywords: business, philosophy and infaq. Ayat dan surat al-Lail asupan penting dalam jajaran ayat-ayat bisnis lewat ayat ini di mana mampu memberikan dalil baru dalam belantika ekonomi. Al-Qur’an dan Hadits merupakan dua pedoman umat muslim yang saling berhubungan satu sama lain. keadaan saat ini maupun keadaan pada masa yang akan datang, juga sarat dengan ilmu pengetahuan dan teknologi yang dibutuhkan oleh umat manusia. Sehingga al-Qur'an dan Hadits sering disebut sebagai sumber segala ilmu pengetahuan termsuk masalah usaha dan muamalat. Ilmu pengetahuan yang terdapat dalam al-Qur'an ada yang mudah dipahami ada juga yang memerlukan pemikiran dan pengembangan serta perenungan lebih lanjut untuk dapat dipahami. Pemahaman tentang al-Qur'an seseorang tergantung pada kecerdasan, sehingga dari ayat yang sama mungkin saja akan memberikan tafsiran yang berbeda.dalam jurnal ini kami membahas hubungan surat al-lail tentang ekonomi dengan filosofinya. Momentum Surat Al-Lail adalah surat Makiyyah yang diturunkan kepada Nabi shalallahu ‘alaihi wasallam sebelum berhijrah ke kota Madinah, dan pokok pembicaraan surat ini berkaitan dengan orang-orang yang berinfak dan orang-orang yang bakhil. Serta motivasi gerak usaha dengan berbagai teori dan praktek.